Apolipoprotein B gene expression and regulation in relation to Alzheimer’s disease pathophysiology - Gabriel Aumont-Rodrigue; Cynthia Picard; Anne Labonté; Judes Poirier (Journal of Lipid Research)
Apolipoprotein B (APOB), a receptor-binding protein present in cholesterol-rich lipoproteins, has been implicated in Alzheimer's disease (AD). High levels of APOB-containing low-density lipoproteins (LDL) are linked to the pathogenesis of both early-onset familial and late-onset sporadic AD. Rare coding mutations in the APOB gene are associated with familial AD, suggesting a role for APOB-bound lipoproteins in the central nervous system. This research explores APOB gene regulation across the AD spectrum using four cohorts: BRAINEAC (elderly control brains), DBCBB (controls, AD brains), ROSMAP (controls, MCI, AD brains), and ADNI (control, MCI, AD clinical subjects). APOB protein levels, measured via mass spectrometry and ELISA, positively correlated with AD pathology indices and cognition, while APOB mRNA levels showed negative correlations. Brain APOB protein levels are also correlated with cortical Aβ levels. A common coding variant in the APOB gene locus affected its expression but didn't impact AD risk or brain cholesterol concentrations, except for 24-S-hydroxycholesterol. Polymorphisms in the CYP27A1 gene, notably rs4674344, were associated with APOB protein levels. A negative correlation was observed between brain APOB gene expression and AD biomarker levels. CSF APOB correlated with Tau pathology in presymptomatic subjects, while cortical APOB was strongly associated with cortical Aβ deposition in late-stage AD. The study discusses the potential link between blood-brain barrier dysfunction and AD symptoms in relation to APOB neurobiology. Overall, APOB's involvement in lipoprotein metabolism appears to influence AD pathology across different stages of the disease.